Development of a CAD system for automatic classification of microcalcifications based on FPGA - Docusse, Tiago A. [UNESP]; Silva, Alexandre C. R. da [UNESP]; Pereira, Aledir S.; Marranghello, Norian (Elsevier B.V., 2013)
This paper presents a Computer Aided Diagnosis (CAD) system that automatically classifies microcalcifications detected on digital mammograms into one of the five types proposed by Michele Le Gal, a classification scheme that allows radiologists to determine whether a breast tumor is malignant or not without the need for surgeries. The developed system uses a combination of wavelets and Artificial Neural Networks (ANN) and is executed on an Altera DE2-115 Development Kit, a kit containing a Field-Programmable Gate Array (FPGA) that allows the system to be smaller, cheaper and more energy efficient. Results have shown that the system was able to correctly classify 96.67% of test samples, which can be used as a second opinion by radiologists in breast cancer early diagnosis. (C) 2013 The Authors. Published by Elsevier B.V.
Keywords: Image classification; Cancer detection; Mammography; Embedded software